2001
DOI: 10.1046/j.1440-1746.2001.02501.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic genotypes and risk for colorectal cancer

Abstract: No strong associations have been found between metabolic genotypes and colorectal cancer risk in Australia. Large studies will be required to confirm weak associations and to establish relationships between cancer risk, metabolic genotypes and exposure to dietary or other environmental carcinogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
1
5

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 20 publications
4
58
1
5
Order By: Relevance
“…[29,[38][39][40][41][42][43][44] . Oncogenes and tumor suppressor genes can also affect individual's susceptibility to cancer [34][35][36]45] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[29,[38][39][40][41][42][43][44] . Oncogenes and tumor suppressor genes can also affect individual's susceptibility to cancer [34][35][36]45] .…”
Section: Resultsmentioning
confidence: 99%
“…The associations between CYP1A1 genotype and susceptibility to cancers were varied [39][40][41][42]47,70] . Data from Guangdong province of China showed that MspI C correlated with lung cancer susceptibility in no-smoking populations [65] .…”
Section: Risk Factors For Ecmentioning
confidence: 99%
“…The different liability to cancer was called genetic susceptibility to cancer. Genetic susceptibility can affect in every step of carcinogenesis, including modifying the effect of environmental carcinogens [9][10][11][12][13] . Cancer susceptible genes include types I and II metabolism enzyme genes, DNA repair gene and those affecting cell proliferation rate.…”
Section: Discussionmentioning
confidence: 99%
“…According to the inclusion criteria, 43 studies (Agúndez et al, 1994;Wundrack et al, 1994;Agúndez et al, 1996;Ladona et al1996;Legrand et al, 1996;London et al, 1997;Agúndez et al, 1998;Febbo et al, 1998; González et al, 1998; Hu et Shaw et al, 1998;Krajinovic et al, 1999;Lemos et al, 1999;Topić et al, 2000;Butler et al, 2001;Liu et al, 2002;Sobti et al, 2003;Chen et al, 2004;Fukatsu et al, 2004;Li et al, 2004;Gajecka et al, 2005;Gomes et al, 2005;Guo et al, 2005;Liang et al, 2005;Mochizuki et al, 2005;Sobti et al, 2005;Aydin-Sayitoglu et al, 2006;Bonanni et al, 2006;Li et al, 2006;Lemos et al, 2007;Chen et al, 2008;Khedhaier et al, 2008;Majumdar et al, 2008;Ouerhani et al, 2008 ;Torresan et al, 2008;Yan et al, 2008;Altayli et al, 2009;Gutman et al, 2009;Lim et al, 2011;Luo et al, 2011;Zhou et al, 2011) appeared to have met the inclusion criteria and were subjected to further examination. The flow chart of study selection is shown...…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%